Impact of smoking on postoperative complications after anterior cervical discectomy and fusion. (April 2017) - Purvis, Taylor E.; Rodriguez, Haroldo J.; Ahmed, A. Karim; Boone, Christine; De la Garza-Ramos, Rafael; Elder, Benjamin D.; Goodwin, C. Rory; Sciubba, Daniel M.
Highlights: Current smokers undergoing ACDF did not have increased odds of complications. Pack-years was not associated with greater odds of developing complications. A positive ever-smoker status was associated with higher odds of complications. ACDF patients with a prior smoking history should be considered higher risk. Abstract: The relationship between smoking and the risk of postoperative complications among anterior cervical discectomy and fusion (ACDF) patients remains uncertain. We compared the postoperative complication rates following ACDF surgery among non-smokers, current smokers, and ever-smokers. Baseline and outcome data were obtained from the 2005- to 2014 American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database for patients over the age of 18 who underwent non-emergent ACDF surgery. Information on current smoking and ever-smoking status was extracted. Outcomes included development of at least one complication, development of a major complication, in-hospital mortality, and length of stay. ACDF patients were either current smokers (7847, 30.3%) or not current smokers (18, 022, 69.7%); 33.0% of all patients ( n  = 8542) had ever smoked. Current smoking status was not associated with increased odds of any one complication ( P  = 0.584) or any major complication ( P  = 0.138). In addition, using the number of pack-years as the primary independent variable, multivariate logistic regression analysis revealed that the number of pack-years was not significantly associated with greater odds of developing any one complication ( P  = 0.276) or any major complication ( P  = 0.334). However, ever-smoker status did present significantly higher odds of any major complication (OR, 1.333; 95% CI 1.007–1.764; P  = 0.044) than for non-smokers. These results suggest that any patient with a prior smoking history should be considered a higher risk surgical candidate when attempting ACDF.